The future of dermatology: integrating artificial intelligence into clinical practice - Almutairi, Nawaf; Al Agraa, Bakri; Mohamed, Zainab (International Journal of Research in Dermatology, 2025)
Dermatology has benefited considerably from the use of artificial intelligence (AI), which has emerged as a crucial tool in healthcare. Algorithms for machine learning (ML) and deep learning (DL), in particular convolutional neural networks (CNNs), have demonstrated significant promise in the diagnosis of skin disorders, classification of lesions, and telemedicine support. The use of AI in dermatology is examined in this paper, with particular attention paid to how it might improve patient care, increase access to dermatological treatments, and improve diagnostic accuracy. It also discusses the difficulties, moral dilemmas, and potential applications of AI in dermatology. It highlights the necessity of cooperation between researchers, practitioners, and regulatory agencies to guarantee a secure and efficient transition into clinical practice.